A Study on the Motivating Factors that Stimulates A Common Man to Become Great Entrepreneurs, with Specific Reference to Madurai City - D. Anbugeetha, Dr.; B. Nandhini, Ms. (International Journal of Engineering and Technology, 2018)
EntrepreneurshipÂ is the process of crafting, establishing and operating a new venture. It is a vibrant process of application of energy to convert creative ideas into reality. It wholly depends upon the decision people make about how to carry out the process and accomplish something in life. The populace that creates these businesses is calledÂ an entrepreneur. They are people who have the competence and keenness to build up, categorize and administer a business along with any of its risks in order to make some returns. Entrepreneurs when motivated exhibit high efficiency. They are creators carrying a huge responsibility of social development, creating something new and better, notably through innovation, thus harmonizing the goals of all stakeholders while sustaining the economic feasibility of a business.People become entrepreneurs for numerous reasons. There may be several factors which trigger individuals to land up into business. This research paper studies and identifies the various factors which motivates a common man of Madurai city to become great entrepreneurs. The various factors which motivated the people of Madurai city to become entrepreneurs were measured. The EMQ developed by Nergis Aziz, Barry A. Friedman, Aichurek Bopieva and Ibrahim Keles, was used to gather data for the present study. The 30 item questionnaire speaks about 7 dimensions of entrepreneurial motives. The study also tries to identify whether there is a difference among the respondents belonging to various demographic profiles on their scores on the various factors of entrepreneurial motives, using simple percentage analysis, t-test and ANOVA.Â Â Â